Changes in the sucrose metabolism in apple fruit following postharvest acibenzolar‐S‐methyl treatment. (19th October 2018) - Ge, Yonghong; Wei, Meilin; Li, Canying; Chen, Yanru; Duan, Bin; Li, Xue; Tang, Qi; Li, Xihong
Abstract: BACKGROUND: Apple (cv. Ralls) fruit were treated with 0.1 g L −1 acibenzolar‐S‐methyl (ASM) for 10 min to evaluate the changes in enzyme activity and gene expression in the sucrose metabolism during storage at 20 °C with 30%–40% relative humidity. RESULTS: The results showed that sucrose phosphate synthase (SPS) and sucrose synthase synthesis (SS‐s) activity was enhanced by ASM in apple fruit during the entire storage period. Sucrose synthase‐cleavage (SS‐c) and neutral invertase (NI) activity was suppressed by ASM treatment but acid invertase (AI) activity was increased in the middle period after ASM treatment. Acibenzolar‐S‐methyl treatment also significantly inhibited SPS and NI gene expression in apple fruit during storage. However, SS gene expression increased in the ASM‐treated apple fruit. High levels of expression of the fructokinase ( FK ) and hexokinase (HK) genes were observed during the middle storage period in the ASM‐treated fruit. CONCLUSION: Taken together, these results suggest that ASM delays the senescence of apple fruit by regulating the sugar metabolism. © 2018 Society of Chemical Industry